The styles of thinking among primary school teachers - Kamarulzaman, Wirawani; Oo, Cheng Keat; Mohd Jodi, Khairul Hamimah; Che Aziz, Raziana; Mahmood, Rosinah (Global Academic Excellence (M) Sdn Bhd, 2021)
According to Malaysian National Philosophy, one of the main goals of education is to help students become well-rounded persons who can think critically. Being aware of how well teachers can impart knowledge and skills is vital because they are the most influential players in the educational process. In other words, the aim of this study is to see if there are any disparities in thinking abilities between male and female professors. 266 primary school teachers in Selangor completed the Teaching Skills Inventory, and the results showed that teachers use executive thinking skills. In spite of the fact that men teachers outperformed female teachers in all of Sternberg's proposed thinking types, a t-test shows that male teachers preferred executive thinking skills. The study's findings were followed up with several recommendations for further investigation.